Length–weight relationships of three fish species from a tropical mangrove estuary of Sarawak, Malaysia - Mustafa Kamal, Abu Hena; Idris, Mohd Hanafi; Rajaee, Amy Halimah; Siddique, Mohammad A. Momin (Blackwell Verlag, 2017)
Length–weight relationships for three mangrove fish species, Setipinna melanochir (Bleeker, 1849), Ilisha elongata (Anonymous [Bennett], 1830), and Nibea soldado (Lacépède, 1802) were determined. Samplings were conducted in a tropical mangrove estuary, Sarawak, Malaysia (3°59′25.76′′N; 113°43′51.6′′E) at the peak of three different seasons using gillnets (100 × 2.5 m, mesh sizes 1, 2 and 4 inches) during 2014–2015. No information regarding length–weight relationships of these species was reported previously in FishBase.